Skin Work: Understanding the Embodied Experience of Acne. (June 2018) - Lafrance, Marc; Carey, R Scott
In this article, we carry out a four-part study of why and how those with acne work on their skin. In the first part, we engage extensively with the clinical literature and reflect critically on what it has to offer. In the second part, we present our notion of 'skin work' and how it allows for a consideration of how acne sufferers relate reflexively to the surface of their bodies. In the third part, we discuss our data – which consists of over 200 threads from the electronic support groupacne.org – and how we approach it in order to better understand the everyday practices associated with working on the skin. Finally, in the fourth part, we discuss our findings by focusing on three prevalent types of skin work and how they both shape and are shaped by identity categories such as gender and sexuality.